2003
DOI: 10.1148/radiol.2272010839
|View full text |Cite
|
Sign up to set email alerts
|

Flat-Panel X-ray Detector Based on Amorphous Silicon versus Asymmetric Screen-Film System: Phantom Study of Dose Reduction and Depiction of Simulated Findings

Abstract: The diagnostic performance of the flat-panel detector is comparable to that of the asymmetric screen-film system for depiction of all simulated patterns of interstitial lung diseases, nodules, and catheters at the same speed and offers the potential of dose reduction to a speed of 800.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In the virtual volume method, the fluctuations in grey-scale levels of images are considered as fractional Brownian motion functions 18 , and the complexity is represented as the logarithm of the mean of virtual volumes with a square base with a length (r) of 1 pixel, because log 10 r = 0 at r = 1 and V(r = 1) = P in the equation (1). Thus, the height of the virtual volume at r = 1 corresponds to the difference in grey-scale levels between the adjacent pixels of digital image, and the mean of the virtual volume at r = 1 is proportional to the mean difference in grey-scale levels between the adjacent pixels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the virtual volume method, the fluctuations in grey-scale levels of images are considered as fractional Brownian motion functions 18 , and the complexity is represented as the logarithm of the mean of virtual volumes with a square base with a length (r) of 1 pixel, because log 10 r = 0 at r = 1 and V(r = 1) = P in the equation (1). Thus, the height of the virtual volume at r = 1 corresponds to the difference in grey-scale levels between the adjacent pixels of digital image, and the mean of the virtual volume at r = 1 is proportional to the mean difference in grey-scale levels between the adjacent pixels.…”
Section: Discussionmentioning
confidence: 99%
“…This advantage is expected to allow reductions in radiation dosage for patients. Thus, a dose reduction level that provides a satisfactory diagnostic image has been investigated intensively [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Various groups [1][2][3][4][5][6][7][8][9][10][11][12][13][14] have evaluated the performance of flat panel detectors using amorphous selenium (a-Se) and silicon (a-Si) for imaging applications using different models and methods. Granfors, et al 6 have evaluated the performance of 28 production a-Si detectors and confirmed that these detectors had a good capability for dynamic imaging in a cardiovascular imaging system.…”
Section: Introductionmentioning
confidence: 99%
“…1 For chest radiographs, the detectability of abnormalities by general FPDs has been compared with that obtained by CR systems and screen-film systems; some studies showed that the FPD was superior for the detectability of some nodules, but other studies showed the detectability of chest abnormalities, including nodules and interstitial pneumonia, to be equal. [2][3][4][5][6] To further improve image quality, irradiation side sampling (ISS) technology was developed and was made commercially available in 2010. 7 In the original indirect FPD, the luminescence converted from the X-rays was attenuated and diffused by the scintillator before photodiodes read it.…”
mentioning
confidence: 99%
“…The chest phantom was divided, by using thin wires, into six pulmonary areas [3][4][5][6]12 ( Figure 2). Mediastinal areas were not included for the observations.…”
mentioning
confidence: 99%